A hybrid validation framework for LLM-enhanced open data service: the mindat API as a use case - Jiyin Zhang; Weilin Chen; Chenhao Li; Xiaogang Ma (Earth Science Informatics, 2026)
Large Language Models (LLMs) enable natural language interfaces for data retrieval, but their tendency to hallucinate hinders their adoption in scientific applications that require high accuracy. Unlike deterministic traditional APIs (Application Programming Interface), LLMs introduce inherent uncertainty, posing critical challenges for reliable geoscience data access. This paper presents OpenMindatAI, a system that leverages a role-specialized LLM pipeline and a hybrid validation framework to generate reliable API requests for Mindat, one of the largest open databases in geoscience. A consensus voting mechanism is implemented to enhance reliability by generating multiple requests simultaneously and proceeding only upon majority agreement. The hybrid validation framework combines rule-based syntactic validation and LLM-based semantic validation to further ensure structural correctness and logical consistency. The performance of OpenMindatAI is evaluated using a synthetically generated benchmark dataset conforming to the Berkeley Function Call Leaderboard (BFCL) specifications. As a result, OpenMindatAI achieved an F1-score of $$97.08%$$ , significantly outperforming the $$83.95%$$ baseline. This work bridges the gap between non-technical users and specialized geoscience data APIs while establishing a foundation for LLM-enhanced data services. Our system serves as a reliable intermediary, enabling external LLM agents to access specialized geoscience data without domain-specific customization, thereby promoting seamless integration of scientific data repositories into the broader LLM ecosystems.

Digraph-based characterization of geological spatiotemporal relationships and its application in three-dimensional structural reconstruction using the DL + MPS framework - Shuwan Ye; Weisheng Hou; Yonghua Chen; Xin Li; Ying Huang (Earth Science Informatics, 2026)

Automated geological modeling with ArcGIS Engine: a methodological framework for surface and subsurface data integration - Guoxu Chen; Suzanne Hurter; Li Cao; Muyuan Lu; Yongqi Fan; Kesheng Zuo (Earth Science Informatics, 2026)

A multi-dimensional modified deep learning framework for predicting potential creep-type landslides based on geological data - Yue Liu; Peihua Xu; Chen Cao; Liling Jin; Bo Han; Rongchen Ma; Chensi Li (Earth Science Informatics, 2026)

TRA: Topological Relation-Aware link prediction in spatial knowledge graphs - Fu Zhang; Qinghui Li; Hongzhi Chen; Tong Shen; Jingwei Cheng; Weijun Li (Earth Science Informatics, 2026)

Predicting offshore downhole rock drillability in complex geological conditions using explainable machine learning and Multi-Source data - Huayang Li; Quanyou Liu; Jiaao Chen; Chi Zhang; Dantong Liu; Zehui Shi; Xinyi Wang (Earth Science Informatics, 2025)

A new method using convolutional neural networks to distinguish basalt tectonic settings: breaking through theErnst constraints of incomplete geochemical datasets - Ming Lei; Jian Li; Wenyan Cai; Qingyi Cui; Xuyan Bian; Dezhou Chen; Zhengyang Zhang (Earth Science Informatics, 2025)

STAT-LSTM: A multivariate spatiotemporal feature aggregation model for SPEI-based drought prediction - Ying Chen; Huanping Wu; Nengfu Xie; Xiaohe Liang; Lihua Jiang; Minghui Qiu; Yonglei Li (Earth Science Informatics, 2025)

EBC-YOLO: a remote sensing target recognition model adapted for complex environments - Huakun Luo; Yuqi Wang; Youlin Chen; Xi Li; Jianhui Zhan; Deng Zuo (Earth Science Informatics, 2025)

An L1 norm regularization model for signal extraction from GNSS coordinate time series - Zhuofan Wang; Gang Chen; Hongwei Li; Jiawen Bian; Jiaqi Zhang (Earth Science Informatics, 2025)

Geomorphological evolution of small watershed on the Chinese Loess Plateau based on slope shape spectra - Hongtao Jiang; Nan Chen; Chen Wang; Sijia Li; Mengyao Ou (Earth Science Informatics, 2025)

Magnetic properties of agricultural soils and their relationships with environmental factors in Jinghong, Yunnan, China - Meichen Wang; Haixia Li; Shiyu Li; Yudong Chen; Gangqiang Li (Earth Science Informatics, 2025)

Segmentation of urban green space and water body based on high-resolution remote sensing images - Chen Yang; Ying Wei; Junwei Liu; Hao Yang; Zhoubang He; Jiaguang Li (Earth Science Informatics, 2025)

High-precision landslide susceptibility assessment based on the coupling of IHAOAVOA algorithm and BP neural network - Siyu Liang; Li Li; Yue Qiang; Xinlong Xu; Wenjun Yang; Tao Chen; Xinyi Tan; Xi Wang (Earth Science Informatics, 2025)

A multi-stage adaptive otsu thresholding algorithm for pore segmentation in rock thin-section images - Chengzhen Yu; Wenhui Wu; Jun Zheng; Wei Zeng; Dongyu Zheng; Zhiwu Li; Caihua Chen; Sheng Wang (Earth Science Informatics, 2025)

Seismic hazard prediction in mining activities using metaheuristic algorithms - Jie Cai; Chunbo Fang; Juncheng Li; Mingang Li; Sheng Chen; Jinwen Zhou (Earth Science Informatics, 2025)

Optimizing landslide susceptibility mapping using integrated forest by penalizing attributes model with ensemble algorithms - Wei Chen; Chao Wang; Xia Zhao; Li Bai; Qingfeng He; Xi Chen; Qifei Zhao; Ruixin Zhao; Tao Li; Paraskevas Tsangaratos; Ioanna Ilia (Earth Science Informatics, 2025)

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

A method for landslide identification and detection in high-precision aerial imagery: progressive CBAM-U-net model - Hanjie Lin; Li Li; Yue Qiang; Xinlong Xu; Siyu Liang; Tao Chen; Wenjun Yang; Yi Zhang (Earth Science Informatics, 2024)

Exploring advanced machine learning techniques for landslide susceptibility mapping in Yanchuan County, China - Wei Chen; Chao Guo; Fanghao Lin; Ruixin Zhao; Tao Li; Paraskevas Tsangaratos; Ioanna Ilia (Earth Science Informatics, 2024)

Two-stage forecasting of TCN-GRU short-term load considering error compensation and real-time decomposition - Yang Li; Yongsheng Ye; Yanlong Xu; Lili Li; Xi Chen; Jianghua Huang (Earth Science Informatics, 2024)

Precipitation nowcasting leveraging spatial correlation feature extraction and deep spatio-temporal fusion network - Wenbin Yu; Yangsong Li; Cheng Fan; Daoyong Fu; Chengjun Zhang; Yadang Chen; Ming Qian; Jie Liu; Gaoping Liu (Earth Science Informatics, 2024)

PID4LaTe: a physics-informed deep learning model for lake multi-depth temperature prediction - Lingling Chen; Li Wang; Weixiang Ma; Xiaoya Xu; Hao Wang (Earth Science Informatics, 2024)

Ontology-driven relational data mapping for constructing a knowledge graph of porphyry copper deposits - Chengbin Wang; Liangquan Tan; Yuanjun Li; Mingguo Wang; Xiaogang Ma; Jianguo Chen (Earth Science Informatics, 2024)

Surface water extraction from high-resolution remote sensing images based on an improved U-net network model - Guoqing Wang; Guoxu Chen; Bin Sui; Li’ao Quan; Er’rui Ni; Jianxin Zhang (Earth Science Informatics, 2024)

Adaptive direct sampling-based approach to ore grade modeling - ZhangLin Li; ShuiHan Yi; Ning Wang; XiaLin Zhang; Qiyu Chen; Gang Liu (Earth Science Informatics, 2024)

Exploring neuro-symbolic AI applications in geoscience: implications and future directions for mineral prediction - Weilin Chen; Xiaogang Ma; Zhe Wang; Wenjia Li; Chao Fan; Jiyin Zhang; Xiang Que; Chenhao Li (Earth Science Informatics, 2024)
The integration of machine learning (ML) and deep learning (DL) into geoscience has experienced a pronounced uptick in recent years, a trend propelled by the intricate nature of geosystems and the abundance of data they produce. These computational methods have been harnessed across a spectrum of geoscientific challenges, from climate modeling to seismic analysis, exhibiting notable efficacy in extracting valuable insights from intricate geological datasets for applications such as mineral prediction. A thorough analysis of the literature indicates a marked escalation in AI-centric geoscience research starting in 2018, characterized by a predictive research orientation and a persistent focus on key computational terms. The thematic network and evolution analyses underscore the enduring prominence of “deep learning” and “machine learning” as pivotal themes, alongside progressive developments in “transfer learning” and “big data”. Despite these advancements, other methodologies have garnered comparatively lesser focus. While ML and DL have registered successes in the realm of mineral prediction, their amalgamation with domain-specific knowledge and symbolic reasoning could further amplify their interpretability and operational efficiency. Neuro-Symbolic AI (NSAI) emerges as a cutting-edge approach that synergizes DL’s robust capabilities with the precision of symbolic reasoning, facilitating the creation of models that are both powerful and interpretable. NSAI distinguishes itself by surmounting traditional ML constraints through the incorporation of expert insights and delivering explanatory power behind its predictive prowess, rendering it particularly advantageous for mineral prediction tasks. This literature review delves into the promising potential of NSAI, alongside ML and DL, within the geoscientific domain, spotlighting mineral prediction as a key area of focus. Despite the hurdles associated with infusing domain expertise into symbolic formats and mitigating biases inherent in symbolic reasoning, the application of NSAI in the realm of critical mineral prediction stands to catalyze a paradigm shift in the field. By bolstering prediction accuracy, enhancing decision-making processes, and fostering sustainable resource exploitation, NSAI holds the potential to significantly reshape geoscience’s future trajectory.

How does extreme point sampling affect non-extreme simulation in geographical random forest? - Hui Wang; Meixu Chen; Zhe Wang; Li Huang; Christopher C. Caudill; Shijin Qu; Xiang Que (Earth Science Informatics, 2024)

Geological structure identification of coalbed methane reservoir based on trend surface and curvature analysis algorithms - Guoxu Chen; Ruirui Li; Li Cao; Fang Lv; Jing Yuan; Panpan Li; Shengdong Liu; Zhongcheng Li (Earth Science Informatics, 2024)

Wildfire susceptibility prediction using a multisource and spatiotemporal cooperative approach - Jiehang Deng; Weiming Wang; Guosheng Gu; Zhiqiang Chen; Jing Liu; Guobo Xie; Shaowei Weng; Lei Ding; Chuan Li (Earth Science Informatics, 2023)

Spectral-spatial dynamic graph convolutional network for hyperspectral image classification - Rong Chen; Guanghui Li; Chenglong Dai (Earth Science Informatics, 2023)

Correction to: Non-normal distribution of radon and residual radon and short-term abnormal precursors of residual radon before major earthquakes - Xiaobing Jin; Junwei Bu; Guilan Qiu; Li Ma; Zhongming Chen; Tao Chen; Junwei Wu; Bo Pan; Hai Ji; Jingxuan Tian; Xiaoxiao Wu; Zhipeng Li; et al. (Earth Science Informatics, 2022)

Land subsidence calculation model under the coupling effect of groundwater and coal mining - Yiguo Xue; Hong Chen; Fanmeng Kong; Zhiqiang Li; Daohong Qiu; Qiqi Chen; Fan Yang; Xudong Jiang (Earth Science Informatics, 2022)

Non-normal distribution of radon and residual radon and short-term abnormal precursors of residual radon before major earthquakes - Xiaobing Jin; Junwei Bu; Guilan Qiu; Li Ma; Zhongming Chen; Tao Chen; Junwei Wu; Bo Pan; Hai Ji; Jingxuan Tian; Xiaoxiao Wu; Zhipeng Li; et al. (Earth Science Informatics, 2022)

Prediction of groundwater level using the hybrid model combining wavelet transform and machine learning algorithms - Aihua Wei; Yuanyao Chen; Duo Li; Xianfu Zhang; Tao Wu; Hui Li (Earth Science Informatics, 2022)

Spatial and temporal changes analysis of air quality before and after the COVID-19 in Shandong Province, China - Huaqiao Xing; Linye Zhu; Bingyao Chen; Jingge Niu; Xuehan Li; Yongyu Feng; Wenbo Fang (Earth Science Informatics, 2022)

The study of mineral mapping in black soil using TASI thermal infrared data, taking the Baiquan area of China as an example - Jiang Chen; Zhizhong Li; Xiaoyan Chen; Huimin Dai (Earth Science Informatics, 2022)

A comparative study of threshold selection methods for change detection from very high-resolution remote sensing images - Huaqiao Xing; Linye Zhu; Bingyao Chen; Chang Liu; Jingge Niu; Xuehan Li; Yongyu Feng; Wenbo Fang (Earth Science Informatics, 2022)

Spatio-temporal evolution and influencing factors of land use in Tibetan region: 1995–2025 - Li chen; Qing wang (Earth Science Informatics, 2021)

Grid algorithm for large-scale topographic oblique photogrammetry precision enhancement in vegetation coverage areas - Chen Wang; Xiaodi Xu; Liangcheng Yu; Heng Li; Jeffrey Boon Hui Yap (Earth Science Informatics, 2021)

A two-level storage strategy for map-reduce enabled computation of local map algebra - Jianbo Zhang; Simin Zhou; Tingnan Liang; Yongchang Li; Caikun Chen; Hao Xia (Earth Science Informatics, 2020)

Improving and evaluating boundary algebra filling for identifying polygon intersections - Chen Zhou; Manchun Li (Earth Science Informatics, 2019)

Method for managing and querying geo-spatial data using a grid-code-array spatial index - Shuang Li; Guoliang Pu; Chengqi Cheng; Bo Chen (Earth Science Informatics, 2019)

Force field driven skeleton extraction method for point cloud trees - Linming Gao; Dong Zhang; Nan Li; Lei Chen (Earth Science Informatics, 2019)

SHRIMPDB: a new geoanalytical database for U-Th-Pb geochronological data from SHRIMP measurements - Yutong He; Di Tian; Ranran Gao; Runlong Fan; Li Yao; Pengfei Chen (Earth Science Informatics, 2018)

A comparison of slope units and grid cells as mapping units for landslide susceptibility assessment - Qianqian Ba; Yumin Chen; Susu Deng; Jiaxin Yang; Huifang Li (Earth Science Informatics, 2018)

CyberConnector: a service-oriented system for automatically tailoring multisource Earth observation data to feed Earth science models - Ziheng Sun; Liping Di; Haosheng Hao; Xiaoqing Wu; Daniel Q. Tong; Chen Zhang; Cora Virgei; Hui Fang; Eugene Yu; Xicheng Tan; Peng Yue; Li Lin (Earth Science Informatics, 2018)

LiDAR-based three-dimensional street landscape indices for urban habitability - Liang Cheng; Song Chen; Sensen Chu; Shuyi Li; Yi Yuan; Yu Wang; Manchun Li (Earth Science Informatics, 2017)

Autonomic visiting in digital 3D scenes - Song Chen; Liang Cheng; Manchun Li (Earth Science Informatics, 2016)

A Map-Reduce based parallel approach for improving query performance in a geospatial semantic web for disaster response - Chuanrong Zhang; Tian Zhao; Luc Anselin; Weidong Li; Ke Chen (Earth Science Informatics, 2015)